Impact of downsizing and restructuring decisions and processes on organisational knowledge and organisational effectiveness: Implications for perceived success - Sitlington, Helen; Marshall, Verena (Promaco Conventions Pty Ltd, 2009)
This study examines the impact of downsizing/restructuring decisions and processes on perceptions of organisational effectiveness, together with perceived levels of organisational knowledge after the downsizing/restructuring event in successful and unsuccessful organisations. The study hypothesises that the impact of these decisions and processes on levels of organisational knowledge are a key determinant of effectiveness in successful post-downsizing and restructuring organisations. The findings show, however, that the significance of these variables is to be found in unsuccessful organisations, rather than their successful counterparts. Organisational downsizing and restructuring is a common response to changed economic circumstances and other environmental influences, with organisations implementing these changes in order to improve their effectiveness. The reasons why, and how, organisations downsize or restructure has a major influence on perceived outcomes. The impact of decisions made and processes undertaken in downsizing and restructuring organisations are examined in this study, hypothesising that such decisions and processes influence retention of organisational knowledge, which in turn may have a significant impact on perceived organisational effectiveness. Respondents to this study are divided into self-nominated ‘successful’ and ‘unsuccessful’ organisations post-downsizing or restructuring, against which the findings are compared and discussed. It will be shown that perceived level of organisational knowledge can be used as a general predictor of organisational effectiveness after downsizing/restructuring; nonetheless, it is the retention of knowledge, rather than its increase, that is necessary for improved outcomes after the occurrence of downsizing and restructuring.